1994
DOI: 10.1002/jso.2930560315
|View full text |Cite
|
Sign up to set email alerts
|

Loss of α1β1 and reduced expression of other β1 integrins and cam in lung adenocarcinoma compared with pneumocytes

Abstract: Alterations in expression of various cell-adhesion molecules have been reported in a variety of malignant tissues. However, little is known about how lung adenocarcinomas differ in CAM expression from the normal lung. We analyzed the expression of integrins alpha 1 beta 1 through alpha 6 beta 1, intercellular adhesion molecule (ICAM)-1, neural cell adhesion molecule (NCAM), and lymphocyte function antigen (LFA)-3, CD44, and the two carbohydrate antigens, Lewisx (Le(x)) and sialosyl-Le-Le(x) of lung adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In a recent study, Roussel et al (1994) reported that transformation of normal alveolar pneumocytes to a malignant phenotype was associated with a loss of integrins and CAMs. CD44 was shown to be expressed in non-small cell lung tumours, squamous metaplasia, basal bronchial epithelial cells and activated type II pneumocytes (Penno et al 1994;Terpe et al 1993Terpe et al , 1994.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, Roussel et al (1994) reported that transformation of normal alveolar pneumocytes to a malignant phenotype was associated with a loss of integrins and CAMs. CD44 was shown to be expressed in non-small cell lung tumours, squamous metaplasia, basal bronchial epithelial cells and activated type II pneumocytes (Penno et al 1994;Terpe et al 1993Terpe et al , 1994.…”
Section: Discussionmentioning
confidence: 98%
“…Actually, integrins are heterodimeric transmembrane molecules that modulate cell adhesion, and consistently reduced expression or altered distribution of such molecules has been reported in colon, lung, pancreas and breast tumors. [38][39][40][41] It is also noteworthy that transfection of the highly metastatic BL6 melanoma cells 42 with the integrin a4 subunit gene was reported to inhibit their metastatic potential in vivo. 19 Concerning the other targeted gene, the dok5 gene, it has been previously shown that another member of the dok family, dok1, positively regulates B16F10 cell mobility ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…By immunohistochemistry, many tumors have been analyzed for the expression and distribution of integrins in comparison to their respective normal tissue counterpart. Despite many heterogeneous results, consistent patterns such as reduced expression or altered distribution of collagen and laminin receptors were observed in colon, lung, pancreas, and breast cancers (Stallmach et al 1992;Roussel et al 1994;Weinel et al 1995;Gui et al 1996). Since laminin and collagen receptors play an important role in attaching cells to the basement membrane, these results suggest that loss of attachment to the basement membrane might be important in tumor development.…”
Section: Cell-substrate Adhesionmentioning
confidence: 80%